Shaft seals for dynamic applications - Horve, Leslie A. (Mechanical engineering (Marcel Dekker, Inc.), 1996)
Describes all seal types used in industry for rotating, oscillating and reciprocating shaft applications. The work details the various practices for radial shaft seal selection, testing and installation recommended by the Society of Automotive Engineers, the Rubber Manufacture's Association, the American Society for Testing and Materials, and the American Society of Tribology and Lubrication Engineers, among others.